“From father to son”: The occupational inheritance of Lăutari musicians. A sociological study (Journal of Comparative Research in Anthropology and Sociology, 2025)
This article examines the processes of professional heritage and socialization among Lăutari, traditional Roma musicians in Romania. Drawing on autoethnographic data and thematic content analysis of interviews published in Formula AS magazine, the study explores how musical skills, cultural knowledge, and professional identities are transmitted across generations. The research confirms the predominantly patrilineal nature of occupational inheritance in this community, but reveals a more complex picture of professional socialization. It highlights the crucial role of immersion in a musical environment from an early age, the importance of family and community networks in facilitating learning, and the often overlooked contributions of women in sustaining these traditions. The study also examines the tensions between traditional modes of transmission and modern educational pathways, reflecting broader social changes affecting the Lăutari community. By focusing on this specific group, the article contributes to sociological discussions on occupational inheritance, cultural capital transmission, and the negotiation of traditional identities in modernizing societies, while also shedding light on the adaptations of a marginalized ethnic minority maintaining their professional traditions in contemporary Romania.
Keywords: Occupational inheritance; Cultural capital transmission; Lăutari; Autoethnography; Thematic content analysis